Application of nonconducting poly(o-aminophenol) films in bioelectrochemistry: a review article - Tucceri, Ismael Ricardo (2016)
Interesting practical uses of nonconducting poly(o-aminophenol) (POAP) films in the fields of bioelectrochemistry are discussed in this paper. Particular emphasis is given to the effects of applied potential, solution pH and interferents on the response current of biosensors based on POAP.